1990
DOI: 10.2329/perio.32.261
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological study in clinically characterized rapidly progressive periodontal disease.

Abstract: Samples of subgingival bacteria were collected from two sites of anteriors with• †6mm deep pockets in each ten patients in a clinically characterized rapidly progressive periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…van Winkelhoff et al (171) demonstrated that the elimination of A. actinomycetemcomitans by hygiene phase therapy and antibiotics from ten generalized early‐onset periodontitis patients resulted in clinical improvement and that the one patient that was still A. actinomycetemcomitans –positive after treatment did not improve clinically. Conversely, Masunaga et al (97) reported that the levels of A. actinomycetemcomitans were not changed by scaling and root planing, and the reduction in pocket depth was due to the elimination of P. intermedia and P. gingivalis .…”
Section: Microbiology Of Generalized Early‐onset Periodontitismentioning
confidence: 96%
See 4 more Smart Citations
“…van Winkelhoff et al (171) demonstrated that the elimination of A. actinomycetemcomitans by hygiene phase therapy and antibiotics from ten generalized early‐onset periodontitis patients resulted in clinical improvement and that the one patient that was still A. actinomycetemcomitans –positive after treatment did not improve clinically. Conversely, Masunaga et al (97) reported that the levels of A. actinomycetemcomitans were not changed by scaling and root planing, and the reduction in pocket depth was due to the elimination of P. intermedia and P. gingivalis .…”
Section: Microbiology Of Generalized Early‐onset Periodontitismentioning
confidence: 96%
“…Lopez et al (90) found A. actinomycetemcomitans in 60% of generalized early‐onset periodontitis patients and 50% of affected sites. However, Vandesteen et al (174), Williams et al (182), Moore et al (104) and Lopez et al (91) did not detect A. actinomycetemcomitans in generalized early‐onset periodontitis patients, and although A. actinomycetemcomitans is present in some patients, other organisms such as P. gingivalis , P. intermedia , F. nucleatum and B. forsythus are found with greater frequency and numbers (73, 97, 118, 141). Listgarten et al (85) reported that A. actinomycetemcomitans serotype b was the most common, followed by serotype a and then serotype c.…”
Section: Microbiology Of Generalized Early‐onset Periodontitismentioning
confidence: 99%
See 3 more Smart Citations